2008
DOI: 10.1364/ol.33.000857
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet upconversion emissions of Gd^3+

Abstract: Under 980 nm excitation, upconversion (UC) emissions in the UV range of 270-320 nm were observed in nanocrystals Y(0.795-x)Gd(x)Yb(0.2)Tm(0.005)F(3) (x=0, 0.1, 0.2, 0.5, and 0.795), which were synthesized through a hydrothermal method. These UC emissions can be assigned to the transitions of (6)I(J), (6)P(J)-->(8)S(7/2)(Gd(3+)), and (3)P(0)/(1)I(6)-->(3)H(6) (Tm(3+)). The energy transfer from Tm(3+) to Gd(3+) plays a crucial role in populating the excited states of Gd(3+). The shortest wavelength of upconverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…3 F 4 and 2.83 for 1 G 4 ! 3 H 6 , respectively, which are consistent with the reported values in the literature [15,18]. This means that the population of the levels 6 P J of Gd 3+ , 1 D 2 and 1 G 4 of Tm 3+ came from five-photon, four-photon, and three-photon upconversion processes, respectively.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…3 F 4 and 2.83 for 1 G 4 ! 3 H 6 , respectively, which are consistent with the reported values in the literature [15,18]. This means that the population of the levels 6 P J of Gd 3+ , 1 D 2 and 1 G 4 of Tm 3+ came from five-photon, four-photon, and three-photon upconversion processes, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the probability of the non-radiative relaxation from the 3 P 2 level to the 3 P 0;1 level of Tm 3+ was found to be much larger than the probability of the radiative transition 3 P 2 ! 3 H 6 in NaYF 4 [15] and YF 3 [18] nanocrystals. Thus, the energy was mainly transferred to 6 I J level of Gd 3+ ions, as the case in the Tm 3+ /Yb 3+ codoped GdF 3 system [19].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[10] the researchers firstly used green lasers (546 and 522 nm) as pump lights and observed UC emissions of Gd 3+ in CsMgCl 3 . Cao et al reported the 6 I J and 6 P J states to the ground state 8 S 7/2 emissions of Gd 3+ in YF 3 with a 980-nm LD as excitation source in 2008 [11]. Later, Qin et al observed the 6 D J levels to the 8 S 7/2 level emissions in GdF 3 under the same measurement conditions [12].…”
Section: Introductionmentioning
confidence: 98%